Pozycja Polski w świetle badań zrównoważonego rozwoju środowiska - Markowska, Małgorzata (Position of Poland in the perspective of environmental sustainable development research, 2006)
Environmental Sustainability Index ESI, presented in the study, may become a good reference point for Poland, in relation to environment protection capability assessment in the coming years. Integration of 76 sets of data, as well as the analysis of the scope of natural resources reserves, past and present levels of pollution, efforts taken up in the field of environment management and social capabilities for the improvement of environmental activities results – in the form of 21 environment protection indicators - make such research feasible. Indicators allow for comparisons in areas which make up five major categories: environmental systems, reduction of environmental stresses, reduction of human exposure to environmental stresses, social and institutional capabilities of reacting to environmental challenges and global management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 128-139